THE CLIMATIC RAMIFICATION OF ARCTIC ICE MELT: A COMPREHENSIVE ANALYSIS (Contemporary Journal of Social Science Review, 2025)
The Arctic, which has long been seen as a secluded and unexplored area of planet, is changing dramatically as a result of climate change. With significant effects on the Arctic   environment as well as the climatic system of areas far outside the Arctic, the thawing of Arctic ice has emerged as one of the most noticeable and concerning sign of global warming. Despite the significant environmental effects of Arctic   ice melting, the regions political and economic dynamics are just as significant. Great nations like the USA, Russia and China hold economic and strategic interests in the Arctic, making it a disputed area. There is frequently an inability in taking significant action to address the urgent problems driven on by Arctic   climate variability as a result of a combination of global power dynamics and environmental reality. This study is to investigate how the loss of Arctic   ice disrupt atmospheric and oceanic patterns, which in turn adds to the destabilization of regional climates, and how the geopolitical and economic interest of major countries imped effective action on climate change in the Arctic. The study aims to offer a thorough grasp of the factors behind Arctic   environmental change and the obstacles to international collaboration in tackling it by examining these aspects.